2009
DOI: 10.1016/j.ccr.2009.07.031
|View full text |Cite
|
Sign up to set email alerts
|

The Tensin-3 Protein, Including its SH2 Domain, Is Phosphorylated by Src and Contributes to Tumorigenesis and Metastasis

Abstract: Summary In cell lines from advanced lung cancer, breast cancer, and melanoma, endogenous tensin-3 contributes to cell migration, anchorage-independent growth, and tumorigenesis. Although SH2 domains have not been reported previously to be phosphorylated, the tensin-3 SH2 domain is a physiologic substrate for Src. Tyrosines in the SH2 domain contribute to the biological activity of tensin-3, and phosphorylation of these tyrosines can regulate ligand binding. In a mouse breast cancer model, tensin-3 tyrosines ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
104
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(110 citation statements)
references
References 39 publications
5
104
1
Order By: Relevance
“…Consistent with our findings, tensins have not been found as part of isolated podosomes. In agreement with previous reports (Qian et al, 2009), we found that GFP-tagged tensin 3 accumulated at focal adhesions of NIH3T3 cells. By contrast, Dock5 showed a spread localization throughout the cell (Fig.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Consistent with our findings, tensins have not been found as part of isolated podosomes. In agreement with previous reports (Qian et al, 2009), we found that GFP-tagged tensin 3 accumulated at focal adhesions of NIH3T3 cells. By contrast, Dock5 showed a spread localization throughout the cell (Fig.…”
Section: Discussionsupporting
confidence: 82%
“…Our results suggest that, with Dock5, tensin 3 could participate in the organization of podosome into superstructures in the osteoclast. Consistent with this idea, tensin 3 can interact with p130Cas (Qian et al, 2009), another known regulator of podosome belt formation in osteoclasts (Nagai et al, 2013) that is regulated by Dock5 (Vives et al, 2011).…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…107 Tensin-3 has been shown to be required for tumorigenesis and metastasis in a number of different cell lines, though its role in squamous cell carcinoma specifically has not been determined. 108 Finally, Zyxin is an adaptor protein containing both LIM domains and SH3 domains. Zyxin has a punctate staining in the cytoplasm of keratinocytes within the normal epidermis; however, this staining re-localizes the the edge of migrating keratinocyte sheets during wound healing.…”
mentioning
confidence: 99%